Nonlinear Dynamics and Chaos in Fractional-Order Hopfield Neural Networks with Delay - Xia Huang; Zhen Wang; Yuxia Li (Advances in Mathematical Physics)
A fractional-order two-neuron Hopfield neural network with delay is proposed based on the classic well-known Hopfield neural networks, and further, the complex dynamical behaviors of such a network are investigated. A great variety of interesting dynamical phenomena, including single-periodic, multiple-periodic, and chaotic motions, are found to exist. The existence of chaotic attractors is verified by the bifurcation diagram and phase portraits as well.